PACE and PACE CAM: Security Issues and Protocol Extensions - Kozieł, Patryk (Politechnika Wrocławska, 2023)
Analysis of security issues of protocols PACE and PACE CAM and discussion on two proposed extensions
Keywords: PAKE; PACE CAM; PACE; PACE extensions; GDPR; security analysis; mutual authentication; proof of presence